RELATIONSHIP BETWEEN WEIGHT AND PHYSICO-MECHANICAL PROPERTIES OF COFFEE GRAINS PRODUCED FROM DIFFERENT HARVEST RIPENING - Yuwana Yuwana; Evanila Silvia; Bosman Sidebang (BPFP Faperta UNIB, 2014)
This research aimed to determine relationships between weight and several physic-mechanical properties of coffee grains. Grains having 12.2% (wet basis) moisture content in average, originated from cherries of different ripening levels identified by green, yellow, red and deep red in colors were used for experiment. Research used regresi linear analysis. Results of experiment indicated that weight of grains positively correlated to length, width, thickness and frontal area with very high values of determination coefficient. Weight of grains correlated positively to sphericity and negatively to porosity. Weight of grains originated from green and red cherries had positive correlation with density whereas weight of grains originated from yellow and deep red cherries possessed no correlation with density. Weight of grains from yellow, red and deep red cherries had negative correlation with true density in contrast weight of grains from green cherries had positive correlation with true density. There were no reliable trend concerning the relationships between weight of grains and coefficient of static friction and angle of repose.